Noncoding RNAs: modulators and modulatable players during infection-induced stress response. (25th January 2021) - Chattopadhyay, Partha; Srinivasa Vasudevan, Janani; Pandey, Rajesh
Abstract: The human genome has an almost equal distribution of unique and transposable genetic elements. Although at the transcriptome level, a relatively higher contribution from transposable elements derived RNA has been reported. This is further highlighted with evidence from pervasive transcription. Of the total RNA, noncoding RNAs (ncRNAs) are significant contributors to the transcriptome pool with sizeable fraction from repetitive elements of the human genome, inclusive of Long Interspersed Nuclear Elements (LINEs) and Short Interspersed Nuclear Elements (SINEs). ncRNAs are increasingly being implicated in diverse functional roles especially during conditions of stress. These stress responses are driven through diverse mediators, inclusive of long and short ncRNAs. ncRNAs such as MALAT1, GAS5, miR-204 and miR-199a-5p have been functionally involved during oxidative stress, endoplasmic reticulum (ER) stress and unfolded protein response (UPR). Also, within SINEs, Alu RNAs derived from primate-specific Alu repeats with ~11% human genome contribution, playing a significant role. Pathogenic diseases, including the recent COVID-19, leads to differential regulation of ncRNAs. Although, limited evidence suggests the need for an inquest into the role of ncRNAs in determining the host response towards pathogen challenge.